In vivo gene therapy with plasmid DNA-Tuberous sclerosis complex-2 (TSC-2) in an oral squamous cell carcinoma - Supriatno Supriatno (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2005)
Background: Tuberous sclerosis complex (TSC) is an inherited syndrome in which affected individuals are at increased risk for developing benign tumors. Mutation of the TSC-2 gene encoding tuberin on chromo-some 16p13.3 give rise to the clinical disorder of tuberous sclerosis characterized by the development of hamartomas.Objectives: In the present study, I conducted to examine whether overexpression of TSC-2 can affect the growth of human oral squamous cell carcinoma (OSCC) which have different expression level of p27K'P'. Methods: I constructed an expression vector containing sense-oriented rat TSC-2 cDNA with pcDNA3.1 (Invitrogen), and transfected to oral squamous cell carcinoma (B88) to regulate the expression of TSC-2 gene in each transfectant. Western blot analysis was carried out to determine the protein level of TSC-2. Therefore, Tumor volume and body weight of nude mice was examined using tumorigenicity assay.Results: Overexpression of TSC-2 exerted the growth inhibitory effect of oral squamous cell carcinoma. Sense-oriented B88-TSC-2 cancer cells, have high expression of p27K'P1. Moreover, tumor induced by TSC2 up-regulated transfectans become much smaller than those of control cells.Conclusion: overexpression of TSC-2 may exert the antitumor effect on oral squamous cell carcinoma through p27K'P' induction. Key word: TSC-2 - transfection - oral squamous cell carcinoma - pcDNA3.1 - mutation.